CTA Annual Report 2005 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
As an organisation, we look forward to ensuring continuity of professional services to our partners and ACP beneficiaries in the coming years as well as continuing with existing endeavours and embracing new opportunities as they may arise.